Muhadatsah Learning Through Drama Performance Student Class IX Muhammadiyah Boarding School - Nisa Fahmi Huda (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2020)
Concept of drama performance used for learning Muhadatsah in class IX Muhammadiyah Boarding School Uses cooperative learning approach and Nadzariystul Wahdah unity approach that is collaborated with the method of drama individual role-playing model (presenting manuscript). The purpose of this research is to know the skills of Ahlaqulqarimah speak Arabic. Because many students that still difficulty in speaking because of the linguistic factors in question include difficulties in studying language science such as Sharaf and nahwu. To distract Ahlaqulqarimah to still think that talking with the Arabic language is not as difficult as imagined or perceived before, in the implementation of the concept of Muhadatsah students given some training exercises (strengthening), namely: movement exercises, vocals, character exercises, and last student learning results must be appreciated or rewarded in the form of drama staging in Arabic. Therefore, to overcome the problem of difficulty in learning the Muhadatsah in daily life by Ahlaqulqarimah Muhammadiyah Boarding School, then researchers offer a method to hone the skills of speech students with stage play using the Arabic language in the performance of drama there is communicative, creative, and fun nature. So that the problems that have been faced student can be overcome